The effects of environmental enrichment on voluntary physical activity and muscle mass gain in growing rats - Sudo, Mizuki; Kano, Yutaka; Ando, Soichi (Frontiers in Physiology, 2023)
Environmental enrichment (EE) for rodents involves housing conditions that facilitate enhanced sensory, cognitive, and motor stimulation relative to standard housing conditions. A recent study suggested that EE induces muscle hypertrophy. However, it remains unclear whether muscle hypertrophy in EE is associated with voluntary physical activity, and the characteristics of muscle adaptation to EE remain unclarified. Therefore, this study investigated whether muscle adaptation to EE is associated with voluntary physical activity, and assessed the changes in the muscle fiber-type distribution and fiber-type-specific cross-sectional area in response to EE. Wistar rats (6 weeks of age) were randomly assigned to either the standard environment group (n = 10) or the EE group (n = 10). The voluntary physical activity of rats housed in EE conditions was measured using a recently developed three-axis accelerometer. After exposure to the standard or enriched environment for 30 days, the tibialis anterior, extensor digitorum longus, soleus, plantaris, and gastrocnemius muscles were removed and weighed. Immunohistochemistry analysis was performed on the surface (anterior) and deep (posterior) areas of the tibialis anterior and soleus muscles. The EE group showed increased voluntary physical activity during the dark period compared with the standard environment group (p = 0.005). EE induced muscle mass gain in the soleus muscle (p = 0.002) and increased the slow-twitch muscle fiber cross-sectional area of the soleus muscle (p = 0.025). EE also increased the distribution of high-oxidative type IIa fibers of the surface area (p = 0.001) and type I fibers of the deep area (p = 0.037) of the tibialis anterior muscle. These findings suggest that EE is an effective approach to induce slow-twitch muscle fiber hypertrophy through increased daily voluntary physical activity.